A project-led framework for coach development in English men's professional football: a Premier League case study - McCarthy, L.; Roberts, C.-M. (International Sport Coaching Journal, 2024)
Coach education and development programmes are central to the professional development experiences of sport coaches. Typically, these programmes are structured and sequenced in a linear pathway, and present an opportunity for certification which can be a prerequisite to practice and/or employment. Increasingly, as learning becomes viewed as part of a coach`s lifeworld, versus simply as a means to an end, education and development provision is beginning to reflect this. This article introduces and explores the Coach Development Institute Programme, part of the Premier League`s Elite Coaching Plan, which seeks to improve the quality of football coaching in English boys`/men`s football by engaging coaches in a 2-year work-based learning opportunity. Built around a core of project-based learning and assessment, coaches are supported as they examine a series of meaningful performance problems in their unique practice environments. Through this work, we demonstrate how theories, concepts, and principles from the adult education and assessment as learning literature might work as they are applied in a coach education and development context. With such sparsity of case-based examples like this within the peer-reviewed literature, we intend that our contribution could inform, promote dialogue, and raise questions about authentically supporting coaches beyond a minimum standard of practice.